2021
DOI: 10.3389/fnmol.2021.657514
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial Connexins in Neurodegenerative Diseases

Abstract: Astrocytes play a crucial role in the maintenance of the normal functions of the Central Nervous System (CNS). During the pathogenesis of neurodegenerative diseases, astrocytes undergo morphological and functional remodeling, a process called reactive astrogliosis, in response to the insults to the CNS. One of the key aspects of the reactive astrocytes is the change in the expression and function of connexins. Connexins are channel proteins that highly expressed in astrocytes, forming gap junction channels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 111 publications
0
24
0
Order By: Relevance
“…Increased Cx43-immunostaining in cortical regions containing b-amyloid plaques has been reported in Alzheimer's disease (AD) [41] and increased Cx43 density has been reported in the caudate nucleus in Huntington's disease (HD) [42]. Altered Cx43 expression has also been reported in Parkinson's disease (PD), amyotrophic lateral sclerosis and demyelinating disorders [5,39,43]. A recent study in cases with ageing-related tau astrogliopathy (ARTAG) found an increase in Cx43 density that correlated with the density of tau pathology [36].…”
Section: Discussionmentioning
confidence: 99%
“…Increased Cx43-immunostaining in cortical regions containing b-amyloid plaques has been reported in Alzheimer's disease (AD) [41] and increased Cx43 density has been reported in the caudate nucleus in Huntington's disease (HD) [42]. Altered Cx43 expression has also been reported in Parkinson's disease (PD), amyotrophic lateral sclerosis and demyelinating disorders [5,39,43]. A recent study in cases with ageing-related tau astrogliopathy (ARTAG) found an increase in Cx43 density that correlated with the density of tau pathology [36].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in connexin’s abundance, distribution, posttranslational modifications and degradation are known to play an important pathophysiological role in several conditions and organs, particularly in the heart and the brain ( Rodríguez-Sinovas et al, 2012 ; Huang et al, 2021 ; Rodríguez-Sinovas et al, 2021 ; Tittarelli, 2021 ). The specific role of mitochondrial connexins in these contexts is less known.…”
Section: Pathophysiological Relevance Of Mitochondrial Connexinsmentioning
confidence: 99%
“…Likewise, the enhanced expression of astrocytic Cx43 is altered in animal models of ALS and PD [175]. As in AD, the high expression of Cx43 is hypothesized to cause excessive release of ATP or glutamate into the extracellular space [175], ultimately leading or contributing to neurodegeneration [176]. Thus, there are many shared features in astrocyte-neuronal communication changes in diverse types of neurodegenerative diseases that may be a consequence of the astrocytic responses to their reactive state.…”
Section: Changes To Gliotransmission In Neurodegenerative Diseases Other Than Admentioning
confidence: 99%